Following in your parents' footsteps? Empirical analysis of matched parent-offspring test scores - Sarah Brown; Steven McIntosh; Karl Taylor (Institute for the Study of Labor (IZA), 2009)
In this paper, we explore whether an intergenerational relationship exists between the reading and mathematics test scores, taken at age 7, of a cohort of individuals born in 1958 and the equivalent test scores of their offspring measured in 1991. Our results suggest that how the parent performs in reading and mathematics during their childhood is positively related to the corresponding test scores of their offspring as measured at a similar age. The results further suggest that the effect of upbringing is mainly responsible for the inter-generational relationship in literacy, while genetic effects seem more relevant with respect to numeracy.
urn:nbn:de:101:1-20090216105
Keywords: J13; J24; 330; Human capital; intergenerational transfers; literacy; numeracy; Humankapital; Generationenbeziehungen; Familie; Bildungsniveau; Kognition; Großbritannien